"Touch‐aware" contact model for peridynamics modeling of granular systems. (20th May 2022) - Mohajerani, Soheil; Wang, Gang
Abstract: This article presents an innovative "touch‐aware" frictional contact model for peridynamics to efficiently simulate the contact behavior between irregularly shaped particles. Conventional short‐range force contact model formulates the contact force field in such a way that leaves a large gap between particles, leading to a softer stiffness of contact and inaccurate simulation of densely packed granular materials. The developed "touch‐aware" contact model initiates the contact force calculation when contacting bodies are in touch, which leaves no gap between contacting bodies and provides a stiffer contact in an accurate and efficient way. It simulates frictional contact behaviors and damping between contacting bodies with irregular shapes. Different examples are given to verify the touch‐aware contact model with theoretical solutions such as Hertz theory of contact, Hertz theory of impact, Coulomb's law and damping formulation. The model is also compared with conventional peridynamics contact model and the discrete element method. Finally, the touch‐aware contact model is used to simulate condensation of an aggregate of irregularly shaped particles. These examples demonstrate excellent capacity of the "touch‐aware" model in simulating packed granular systems.